Videodrome, a Ghost Story - Ferrara, Annalaura (Aisthesis, 2025)
The following article offers an analysis of the movie Videodrome. It provides an analysis from a phantasmal point of view. We try to highlight two aspects: the phantasmal content of visual products and the psychic phantasms that they are able to arouse. This conceptual apparatus will be the basis for an analysis of the use and construction of images in photojournalistic contexts.